Evidence of indiscriminate fishing effects in one of the world’s largest inland fisheries - Peng Bun Ngor (Nature Portfolio, 2018)
Abstract While human impacts like fishing have altered marine food web composition and body size, the status of the world’s important tropical inland fisheries remains largely unknown. Here, we look for signatures of human impacts on the indiscriminately fished Tonle Sap fish community that supports one of the world’s largest freshwater fisheries. By analyzing a 15-year time-series (2000–2015) of fish catches for 116 species obtained from an industrial-scale ‘Dai’ fishery, we find: (i) 78% of the species exhibited decreasing catches through time; (ii) downward trends in catches occurred primarily in medium to large-bodied species that tend to occupy high trophic levels; (iii) a relatively stable or increasing trend in catches of small-sized species, and; (iv) a decrease in the individual fish weights and lengths for several common species. Because total biomass of the catch has remained remarkably resilient over the last 15 years, the increase in catch of smaller species has compensated for declines in larger species. Our finding of sustained production but altered community composition is consistent with predictions from recent indiscriminate theory, and gives a warning signal to fisheries managers and conservationists that the species-rich Tonle Sap is being affected by heavy indiscriminate fishing pressure.